Optimisation of fuel cycle for IGNITOR tokamak at TRINITI in Russia: A critical review. (13th November 2020) - Rozenkevich, M.; Perevezentsev, A.; Subbotin, M.; Candido, L.; Testoni, R.; Zucchetti, M.
Abstract: This work reviews the further development of the Italian–Russian bilateral project IGNITOR. One of the primary tasks for the execution of the project is the determination of the different types of engineering systems that will be required to support the engineering infrastructure of the IGNITOR tokamak. The tritium fuel cycle and detritiation systems, which provide tritium reprocessing and confinement during the operation of the scientific program, will be the most important systems. For the location of the IGNITOR, Russia proposed the Troitskii Institute and Thermonuclear Research (TRINITI) site near Moscow. The scope of this work is the investigation of the engineering concept of the tritium fuel cycle and detritiation systems for air and water with regard to the operation of the IGNITOR with tritium plasma at the TRINITI site. Highlights: Technological capabilities for IGNITOR tokamak fusion reactor were reviewed. Optimised configuration of fuel cells for IGNITOR was proposed. Replacement gas chromatography is ideal for hydrogen isotope separation. Proposed to use CECE technology for water detritiation. Proposed to carry out gas stream detritiation using of scrubber column.